2019
DOI: 10.24203/ajhss.v7i4.5856
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Perceived Stress on the Alcohol Consumption of the Filipino Migrant Workers in South Korea

Abstract: This study explored how perceived stress and other common characteristics affected the alcohol consumption of the Filipino migrant workers in South Korea. 201 Filipino migrant workers (78.1% male, 21.9% female) completed the questionnaire containing the Perceived Stress Scale (PSS) for measuring perceived stress and Alcohol Use Disorders Identification Test-C (AUDIT-C) for measuring hazardous drinking.  Pearson’s correlation, regression analysis, T-test and ANOVA were used for statistical analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Moreover, the present study also reported that some individuals are more likely to pursue negative coping behaviour such as cohabitating with someone without marriage to reduce housing costs and to cope with their mental and various challenges, leading to various health determinants such as unwanted pregnancy, HIV, and AIDS. Furthermore, other individuals use alcohol and smoking to deal with their problems that determine their health and well-being, as revealed by previous research among Myanmar migrant workers in Thailand (33) among Filipino irregular migrant workers in Korea (34).…”
Section: Social Determinant Of Health: Coping Behavioursmentioning
confidence: 90%
“…Moreover, the present study also reported that some individuals are more likely to pursue negative coping behaviour such as cohabitating with someone without marriage to reduce housing costs and to cope with their mental and various challenges, leading to various health determinants such as unwanted pregnancy, HIV, and AIDS. Furthermore, other individuals use alcohol and smoking to deal with their problems that determine their health and well-being, as revealed by previous research among Myanmar migrant workers in Thailand (33) among Filipino irregular migrant workers in Korea (34).…”
Section: Social Determinant Of Health: Coping Behavioursmentioning
confidence: 90%